Anger, Compassion, and One Body. Issue 4 (2nd October 2021) - Wong, David B.
ABSTRACT: The issue of conceptual templates of Western philosophy has been prominently put forth by Kwong-loi Shun. This paper seeks to establish additional perspectives adopted in traditional concepts involving anger and compassion by both Confucianist and Western scholars to reconcile purported differences between Confucianist and Western interpretations of key concepts utilised in philosophical thought. Through reinforcing similarities between the different concepts, the author serves to highlight the inter-compatibility of Confucianist and Western interpretations of basic notions of anger and compassion and the need to explore the relevance of both facets in the complex modern world.